The Contribution of 68Ga Prostate-Specific Membrane Antigen Positron Emission Tomography/Computed Tomography Imaging to Detecting Brain Metastasis in Prostate Cancer - Bilgiç, Seçkin (Cerrahpaşa Medical Journal, 2024)
Cite this article as: Bilgiç S. The contribution of 68Ga PSMA PET/CT imaging to detecting brain metastasis in prostate cancer. Cerrahpaşa Med J. 2024;48(2):197-198.